A promising strategy for fabricating high-performance stereocomplex-type polylactide products via carbon nanotubes-assisted low-temperature sintering. (24th January 2019) - He, Shiwen; Bai, Hongwei; Bai, Dongyu; Ju, Yilong; Zhang, Qin; Fu, Qiang
Abstract: Recently, powder metallurgy inspired low-temperature (below the melting temperature) sintering has been proposed as an innovative technology for the processing of eco-friendly stereocomplex-type polylactide (SC-PLA) from its nascent powder, without triggering noticeable thermal degradation. The physicochemical performances of the obtained SC-PLA products are governed by the newly formed SC crystallites with a remarkable ability to weld the interfaces between adjacent powder particles, however, the insufficient interdiffusion of poly(L-lactide) (PLLA) and poly(D-lactide) (PDLA) chains across the interfaces makes it challenging to form sufficient amounts of new SC crystallites. In the present work, we describe a facile and robust strategy to address this challenge by coating a trace amount (e.g., 0.001 wt%) of disentangled carbon nanotubes (CNTs) on the SC-PLA particle surfaces. During the subsequent sintering, these interface-localized CNTs can function as efficient nucleating agent to substantially promote the SC crystallization of PLLA/PDLA chains on their surfaces and finally countless SC crystallites are formed to strongly weld the interfaces as welded joints. Accordingly, SC-PLA/CNTs products possessing superb heat/solvent resistances and mechanical strength have been fabricated. Impressively, with the introduction of 0.001 wt% CNTs, the tensile strength is significantly enhanced from 45.8 MPa to 67.2 MPa. Most importantly, there is a linear relationship between the tensile strength and the content of the CNTs induced SC crystallites. Overall, this wok could provide a practical guidance for the design and fabrication of high-performance SC-PLA products through low-temperature sintering assisted by nanofillers like CNTs. Graphical abstract: Image 1 Highlights: SC-PLA products with superb performances has been fabricated by CNTs assisted low-temperature sintering. The disentangled CNTs were coated on the surface of SC-PLA powder particles before sintering. These CNTs can substantially promote SC crystallization across particle interfaces as nucleating agent. Countless new SC crystallites are induced to strongly weld the interfaces and thus enhance the product performances. The linear relationship between tensile strength and CNTs induced SC crystallites has been established.